Detection and Genotoxicity of Ochratoxin A (OTA) in Raisins - Lerda, Daniel; Miotti, Eduardo; Litterio, Nicolas (European Scientific Journal, ESJ, 2017)
Ochratoxin A (OTA) is a mycotoxin that contaminates a wide variety of foods such as cereals, beer, wine, coffee, cocoa, grapes, raisins and spices. It possibly affects the genetic material of organisms that are in contact with the OTA, causing mutation in their DNA. The aim of this study was to evaluate the presence of the OTA-producing fungi in raisins, its detection and the induction of chromosomal aberrations using the Allium cepa test. Samples of dried grapes were studied in which the microflora and the presence and content of OTA were determined. Allium cepa roots were exposed to OTA content (12 and 15 ng ml-1) for 48 h. Then they were collected from each assay and analyzed. OTA induces alterations in the genetic material of plant cells which suggests that OTA presents genotoxic effects at the concentration studied.